Impact of nitric oxide synthase 2 gene variant on risk of anti-tuberculosis drug- induced liver injury in the Malaysian population - Vishala Sivapalan; Shamsul Mohd Zain; Jin, Shengnan; Chan, Sze Ling; Liu, Jiajun; Zahurin Mohamed; Rosmawati Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2020)
Liver injury is a great threat associated with anti-tuberculosis (anti-TB) medication. Genetic variations in genes encoding drug-metabolising enzymes further enhance this threat. We aimed to explore genetic contributions by evaluating the impact of single nucleotide polymorphisms (SNPs) within the anti-tuberculosis (AT) metabolism pathway genes and within their respective chromosomes on anti-tuberculosis drug- induced liver injury (AT-DILI). Patients (n= 90) were recruited and 170 SNPs were genotyped using Illumina array and validated using Sanger Sequencing. The well-studied N-acetyltransferase 2 (NAT2*6) rs1799930 and cytochrome P450 2E1 (CYP2E1) C1/C1 were not significantly associated with AT-DILI in our cohort but nitric oxide synthase (NOS2A) rs11080344-C was found to be significantly higher in the cases than the controls (OR 2.73, 95% CI 1.12-6.64, P= 0.027). Association studies on all other SNPs within the anti-tuberculosis metabolism pathway genes and within their respective chromosomes also found no significant report. Our study suggests that genetic variation in NOS2A could influence the occurrence of AT-DILI.